Analisis Prosedur Pengelolaan Dana Pensiun Melalui Aplikasi Dapenbun Online Pada PT Perkebunan Nusantara III Medan - Syahputri, Kharisma; Aisyah, Siti (Papanda Publisher, 2024)
Pension funds are an important element in ensuring the sustainability of employee welfare in old age. PT Perkebunan Nusantara III (Persero), a state-owned company operating in the plantation sector, faces challenges in managing pension funds involving thousands of active and retired employees. In an effort to improve efficiency and transparency, the company adopted the Dapenbun Online application as a technology-based solution. This study aims to analyze pension fund management procedures at PT Perkebunan Nusantara III (Persero) Medan City using the Dapenbun Online application. The data obtained in this study were collected through in-depth interviews, literature studies, and direct observation of the Dapenbun Online application. The results showed that the Dapenbun Online application has had a significant impact on the administration process, calculation of pension benefits, and financial reporting. On the other hand, some challenges remain, such as the need to optimize application features and increase digital literacy among users, both active employees and retirees.